2013
DOI: 10.1186/1471-244x-13-107
|View full text |Cite
|
Sign up to set email alerts
|

Association study of OPRM1 polymorphisms with Schizophrenia in Han Chinese population

Abstract: BackgroundThe expression of μ-opioid receptor has important role in cognitive dysfunction in Schizophrenia (SZ). The results of studies about the association of polymorphisms of μ-opioid receptor gene (OPRM1) with SZ were inconsistent.MethodsWe conducted a case–control study to investigate the genetic association between OPRM1 polymorphisms and SZ among the Han chinese population. 264 SZ patients and 264 age-matched control subjects were recruited. Four SNPs of OPRM1 were successfully genotyped by using PCR-RF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 52 publications
1
17
2
Order By: Relevance
“…One study reported lowered MOR availability in the brain of SCZ patients who died as a result of suicide, which would be consistent with increased levels of EOS peptides occupying those receptors (Scarr et al, 2012). Our negative findings on β-endorphin levels in SCZ are not in agreement with those of a previous report (Ding et al, 2013). Animal models of SCZ are accompanied by moderate alterations in EOS peptides (Ashok et al, 2019;Schwarzer et al, 2009;Volk et al, 2011;Szűcs et al, 2016;).…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…One study reported lowered MOR availability in the brain of SCZ patients who died as a result of suicide, which would be consistent with increased levels of EOS peptides occupying those receptors (Scarr et al, 2012). Our negative findings on β-endorphin levels in SCZ are not in agreement with those of a previous report (Ding et al, 2013). Animal models of SCZ are accompanied by moderate alterations in EOS peptides (Ashok et al, 2019;Schwarzer et al, 2009;Volk et al, 2011;Szűcs et al, 2016;).…”
Section: Discussioncontrasting
confidence: 62%
“…Volk et al found that increased MOR mRNA and protein levels in SCZ are largely independent of illness severity, suggesting that increased MOR expression is part of the disease process rather than a consequence of illness chronicity (Volk et al, 2011). In Han Chinese, a MOR polymorphism may confer risk for SCZ (Ding et al, 2013) while an A118G polymorphism of the MOR gene was associated with SCZ (Šerý et al, 2010). One study reported lowered MOR availability in the brain of SCZ patients who died as a result of suicide, which would be consistent with increased levels of EOS peptides occupying those receptors (Scarr et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies revealed that genetic variants in OPRM1 could modulate the dependence to multiple drugs or chemical agents, including nicotine, cocaine, alcohol [25][26][27]. Due to these properties, OPRM1 has been reported associated with the progression of Alzheimer's disease, Parkinson's disease, Schizophrenia and so on [28][29][30]. In lung cancer, Lennon FE et al found that OPRM1 (also known as MOR) expression was elevated in several human non-small cell lung cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies have focused on the A118G allele of hMOR, which changes the amino acid Asn to Asp (N40D) in the N-terminus of the hMOR protein (Campa, Gioia, Tomei, Poli, & Barale, 2008;Ding et al, 2013;Dlugos et al, 2011;Gong et al, 2013;Hastie et al, 2012;Hernandez-Avila et al, 2007;Hishimoto et al, 2008;Manini, Jacobs, Vlahov, & Hurd, 2013;Matsunaga et al, 2009;Menon et al, 2012;Olsen et al, 2012;Ray et al, 2011;Weerts et al, 2013). The location of numerous hMOR SNPs to the 5 0 -untranslated region (5 0 UTR) and upstream promoter regions as well as 3 0 UTR regions of hMOR do not affect the receptor structure but do alter the expression of hMOR and may explain individual differences in pain sensitivity, drug dependency, and the clinical efficacy of morphine (Klepstad, Dale, Skorpen, Borchgrevink, & Kaasa, 2005;Mayer & Hollt, 2006;Uhl, Sora, & Wang, 1999).…”
Section: Variation In Human Opioid Receptor Genesmentioning
confidence: 99%